Abnormalities of potassium metabolism in the practice of the family doctor - Kokot, Franciszek; Hyla-Klekot, Lidia (Przewodnik Lekarza/Guide for GPs, 2008)
Progress in pharmacotherapy in the last 20 years is the reason for the increasing number of drugs used by practitioners which may influence potassium metabolism at the kidney or gastrointestinal level or the transmembrane transport of K + at the cellular level. This may be the cause of life-threatening clinical settings. Hypokalaemia is most often caused by loss of this electrolyte by the kidneys (thiazide, thiazide-like and loop diuretics, glucocorticoids) or gastrointestinal tract (laxantia, diarrhoea, vomitus, external fistula) or may be the result of increased intracellular potassium influx induced by sympathicomimetics mostly used by asthmatics or by insulin overdosage by diabetics. The leading symptoms of hypokalaemia are cardiac arrhythmias. Hyperkalaemia may be caused by acute or end-stage renal failure, by impaired tubular excretion of K + (blockers of the renin-angiotensin-aldosterone system, non-steroidal anti-inflammatory drugs, cyclosporin, antifungal drugs, potassium-sparing diuretics) or by severe cellular injury (tumour lysis syndrome). Hyperkalaemia may be the cause of severe injury of both striated and smooth muscle cells. The specific antidote counteracting hyperkalaemia is a bolus injection of calcium salts and, when necessary, haemodialysis.